Implementation of Load Balancing With PCC Method And Failover Using Mikrotik At PT. Maxpower Indonesia - Putra, Andityo; Anton, Anton (Universitas Trilogi, 2024)
In connecting to a single Internet Service Provider (ISP), one must consider the possibility of network congestion due to high traffic as well as potential disruptions in the internet connection. Load Balancing Per Connection Classifier (PCC) is a method used in combining two ISP services. In supporting day-to-day operational activities, a reliable internet connection is crucial for any company. Therefore, it is also necessary to have an internet connection that remains standby without interruption when there are disruptions in the ISP. This paper discusses the merging of two internet services and the addition of failover techniques. In the first test, a load test was carried out with 1 ISP service. The second test was carried out using two ISP services with the PCC method in high internet traffic conditions. By using the ISP and PCC method, traffic can be reduced and charged to both ISPs so that the network is not burdened by just one ISP. In the second test, it can also be proven that the use of two ISP services with failover techniques is much better when a problem occurs at one of the ISPs, thereby reducing the company's operational impact.